Proceedings of the 2016 ACM Workshop on Artificial Intelligence and Security 2016
DOI: 10.1145/2996758.2996770
|View full text |Cite
|
Sign up to set email alerts
|

Tracked Without a Trace

Abstract: Behavior-based tracking is an unobtrusive technique that allows observers to monitor user activities on the Internet over long periods of time-in spite of changing IP addresses. Previous work has employed supervised classifiers in order to link the sessions of individual users. However, classifiers need labeled training sessions, which are difficult to obtain for observers. In this paper we show how this limitation can be overcome with an unsupervised learning technique. We present a modified k-means algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We show that the learned representations are to some degree task-agnostic, meaning that even though the CNN has to be trained on a specific task (such as predicting disease states from images), the representations capture considerably more information than what is necessary to perform the specific transfer task. In the context of two-sample testing, a recent study has shown both theoretically and empirically that a similar transfer-hypothesis testing approach yields valid p-values and exhibits high statistical power [24].…”
Section: System and Methodsmentioning
confidence: 99%
“…We show that the learned representations are to some degree task-agnostic, meaning that even though the CNN has to be trained on a specific task (such as predicting disease states from images), the representations capture considerably more information than what is necessary to perform the specific transfer task. In the context of two-sample testing, a recent study has shown both theoretically and empirically that a similar transfer-hypothesis testing approach yields valid p-values and exhibits high statistical power [24].…”
Section: System and Methodsmentioning
confidence: 99%
“…For the baseline, in unsupervised learning setting, the stateof-the-art to the author's knowledge is the K-means based method [53]. We use an off-the-shelf K-means implementation [54], with input features formed from cascading the 200 × 2 bits traffic states and the 72 × 2 real value CSI (real and imaginary number as two independent channels).…”
Section: B Unsupervised Device Identificationmentioning
confidence: 99%
“…Both methods use the two multi-layer features (traffic states and PHY CSI) without using the label information. The baseline follows[53].…”
mentioning
confidence: 99%
“…However, encrypted DNS has only recently gained traction with the standardisation of DNS over TLS (DoT) [3] and DNS over HTTPS (DoH) [4], where in today's Internet unencrypted DNS resolution using DNS over UDP (DoUDP) remains the default [5]. Hence, despite the encryption of the actual Web content, the browsing behaviors of individuals can still be observed, enabling third parties to create trackable user profiles [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%